PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN DAN LEVERAGE SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jovial Budi Ramadhani; Lalu Hamdani Husnan; I Nyoman Nugraha AP (Master of Management, Mataram University, 2020)
This study aims to analyze the effect of profitability on stock prices with dividend and leverage policies as moderating variables in the consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX). The independent variable used is Profitability (ROA), with dividend policy (DPR) and leverage (DER) as a moderating variable. The dependent variable is the stock price. The sampling technique was purposive sampling in order to obtain a total sample of 8 companies, with the study period during 2010-2016. This type of research is associative causal. The data analysis technique in this study is moderated regression analysis (MRA) using SPSS. The results of this study indicate that profitability has no effect on stock prices. Dividend policy is proven to be able to strengthen the influence of profitability on stock prices. And leverage is proven to not be able to moderate the effect of profitability on stock prices.Keywords: Profitability, Stock Prices, Dividend Policy, Leverage